(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to examine the health and behavioral effects of carrying schoolbags among primary school pupils, as perceived by their parents, and to assess parents’ awareness of appropriate selection criteria. The sample included 90 parents from three primary schools in the Al-Andalus municipality of Tripoli, using a questionnaire to collect data. Results revealed that 96.7% of children had no prior health symptoms before school enrollment, yet symptoms appeared after starting school and were directly linked to heavy schoolbags (70%). Fatigue and exhaustion were concentrated in the hands and arms (63.3%), affecting other body parts. Moreover, 82.2% of parents acknowledged the health risks of excessive bag weight, while 57.8% of children reported anxiety and stress. Although 88.9% of parents showed concern for body structure and bag content, aesthetic and social factors, along with children’s preferences, often overshadowed health standards. These findings highlight the need to balance health considerations with aesthetic and social aspects when choosing schoolbags.